Ensiklopedi kebudayaan Jawa - Purwadi, 1971- (Yogyakarta : Bina Media, 2005)
Encyclopedia of Javanese culture
Indonesian and Javanese
Keywords: Javanese (Indonesian people) -- Social life and customs -- Encyclopedias; Java (Indonesia) -- Social life and customs -- Encyclopedias; Java (Indonesia) -- Civilization -- Encyclopedias